KUALITAS NUTRIEN PERAIRAN TELUK HURUN, LAMPUNG - Santoso, Arif Dwi (Jurnal Teknologi Lingkungan, 2006)
Some rivers that flow into Hurun Bay waters, agriculture, fishery andhuman settlement and floating cage and oysters faming could benegative impact to waters organisms. Waters fertility is one of somefactors that support the action of determining waters quality. Somenutrient chemistry parameters (anmonia, nitrite, nitrate and phosphate)were analyzed base on specific methods for the parameters. Thenutrient concentrations were variated, for the parameters respectively,ammonia between 4.38 – 23.91 μg/L, nitrite 0.24 – 6.34 μg/L, nitratebetween 1.11 – 7.81 μg/L, and phosphate between 2.17 – 5.75 μg/L.At that moment, the nutrients concentrations were still good for marinewaters category. The environment condition at waters surrounding(river flow, agriculture, human settlement and fishery industry) did notinfluenced to nutrient concentrations.